RETRACTED ARTICLE: Alamandine attenuates hypertension and cardiac hypertrophy in hypertensive rats - Chi Liu; Chuan-Xi Yang; Xi-Ru Chen; Bo-Xun Liu; Yong Li; Xiao-Zhi Wang; Wei Sun; Peng Li; Xiang-Qing Kong (Amino Acids)
Abstract Oral administration of the peptide alamandine has antihypertensive and anti-fibrotic effects in rats. This work aimed to determine whether subcutaneous alamandine injection would attenuate hypertension and cardiac hypertrophy, and improve the function of a major target of hypertension-related damage, the left ventricle (LV), in spontaneously hypertensive rats (SHRs). This was examined in vivo in SHRs and normotensive rats subjected to 6-week subcutaneous infusion of alamandine or saline control, and in vitro in H9C2-derived and primary neonatal rat cardiomyocytes treated with angiotensin (Ang) II to model cardiac hypertrophy. Tail artery blood pressure measurement and transthoracic echocardiography showed that hypertension and impaired LV function in SHRs were ameliorated upon alamandine infusion. Alamandine administration also decreased the mass gains of heart and lung in SHRs, suppressed cardiomyocyte cross-sectional area expansion, and inhibited the mRNA levels of atrial natriuretic peptide and brain natriuretic peptide. The expression of alamandine receptor Mas-related G protein-coupled receptor, member D was increased in SHR hearts and in cardiomyocytes treated with Ang II. Alamandine inhibited the increases of protein kinase A (PKA) levels in the heart in SHRs and in cardiomyocytes treated with Ang II. In conclusion, the present study showed that alamandine administration attenuates hypertension, alleviates cardiac hypertrophy, and improves LV function. PKA signaling may be involved in the mechanisms underlying these effects.